In situ sampling and speciation method for measuring dissolved phosphite at ultratrace concentrations in the natural environment. (15th June 2018) - Han, Chao; Williams, Paul N.; Ren, Jinghua; Wang, Zhaode; Fang, Xu; Xu, Di; Xie, Xianchuan; Geng, Jinju; Ma, Lena Q.; Luo, Jun
Abstract: Phosphite (P +III ) is of emerging chemical interest due to its importance within the global phosphorus cycle. Yet, to date, precise/accurate measurements of P +III are still lacking due to the inherent analytical challenges linked to its instability/ease of oxidation and ultra-trace concentration. Here, we present the first in-situ sampling and speciation analysis method, for dissolved P +III, using the diffusive-gradients-in-thin-films (DGT) technique, combined with capillary-column-configured-dual-ion-chromatography (CC-DIC). Method optimization of the DGT elution regime, to simultaneously maximize desorption efficiency and CC-DIC sensitivity, along with the characterization of diffusion coefficients for P +III, were undertaken before full method validation. Laboratory-performance testing confirmed DGT-P +III acquisition to be independent of pH (3.0–10.0) and ionic strength (0–500 mM). The capacity for P +III was 45.8 μg cm −2, while neither P +V (up to 10 mg L −1 ) nor As +V (up to 1 mg L −1 ) impacted the DGT-P +III measurement. This novel method's functionality stems from the herein confirmed speciation preservation and double pre-concentration of P +III, resulting in quantification limits as low as 7.44 ng L −1 for a 3-day deployment. Applications of this method in various terrestrial/aquatic environments were demonstrated and simultaneous profiles of P +III and P +V across a sediment-water interface were captured at mm resolution in two contrasting redox-mesocosm systems. Graphical abstract: Highlights: In situ selective method for P +III quantification was firstly developed. The diffusion coefficient of P +III through polyacrylamide gel was firstly reported. The method functioned across a wide range of environmental interferences. Successful in situ applications were demonstrated in field environment. Accurate high-resolution profiles of P +III /P +V were captured simultaneously.